2017
DOI: 10.4329/wjr.v9.i3.143
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography pulmonary angiography using a 20% reduction in contrast medium dose delivered in a multiphasic injection

Abstract: AIMTo evaluate the feasibility of reducing the dose of iodinated contrast agent in computed tomography pulmonary angiography (CTPA).METHODSOne hundred and twenty-seven patients clinically suspected of having pulmonary embolism underwent spiral CTPA, out of whom fifty-seven received 75 mL and the remaining seventy a lower dose of 60 mL of contrast agent. Both doses were administered in a multiphasic injection. A minimum opacification threshold of 250 Hounsfield units (HU) in the main pulmonary artery is used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…Thus, they were excluded from the quantitative evaluation. Various human studies have attempted the quantitative assessment of CT angiography, and these studies considered an optimal attenuation value greater than 250 HU [6,23,26]. In our study, enhancement in the PA and PV groups was superior to that in the CA group during the quantitative evaluation.…”
Section: Discussionmentioning
confidence: 61%
“…Thus, they were excluded from the quantitative evaluation. Various human studies have attempted the quantitative assessment of CT angiography, and these studies considered an optimal attenuation value greater than 250 HU [6,23,26]. In our study, enhancement in the PA and PV groups was superior to that in the CA group during the quantitative evaluation.…”
Section: Discussionmentioning
confidence: 61%
“…Computed tomography pulmonary angiography is a European Society of Cardiology guidelines class I indication for ruling out pulmonary embolism, the diagnosis of which is based on acceptable opacification of the main pulmonary artery [ 12 ]. This threshold has been described as > 250 HU, with suboptimal opacification relating to inferior detection for pulmonary embolisms [ 13 , 14 ]. This basic concept can be crudely reduced to discriminating densely opacified pulmonary artery lumen and a less densely attenuating thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…15 Our protocol utilised a concentration of 350 mg iodine/mL, which has been shown to be superior to lower concentrations. 16,17 It can, therefore, be postulated that IV cannula size should only impact contrast opacification when it restricts flow rate. The recommended minimum flow rate for general CT angiograms is 3 mL/s, 14 while a flow rate of 4 mL/s or higher has been recommended for CTPAs internationally.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the finding by Goble et al 17 who found no significant difference in rates of inadequate contrast opacification between 100 mL and 75 mL (350 mg/mL) contrast volume when using a cut-off value of 250 HU. Another study by Chen et al 16 found no significant difference in the rate of inadequately opacified studies between 75 mL and 60 mL (350 mg/mL) contrast volume, also using 250 HU as the cut-off. Individualised contrast volume protocols according to body weight can achieve a reduction in contrast volume while increasing pulmonary arterial enhancement.…”
Section: Number Of Paɵents (N = 130) Flow Rate (Ml/s)mentioning
confidence: 94%